Investigating the ability of shunt hybrid power filter based on SRF method under non-ideal supply voltage - Mohamed A., Omran; Izzeldin, I. Mohd; Mohamad M., Almelian; Sheikh, Usman Ullah; Bofares, Mustafa E. A. A. (IOP Publishing, 2018)
This study presents the capacity of a self-tuning filter based on the synchronous reference frame method with a fuzzy logic controller for the improvement of the efficiency of harmonic suppression of a shunt hybrid active power filter in an unbalanced distorted and un-distorted voltage supply conditions. The simulation results indicated that the filter with a fuzzy logic controller had a good filtering performance in steady and transient states, irrespective of whether the voltage supply is distorted or unbalanced.